2017
DOI: 10.1111/ap.12282
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Dignity Therapy Research

Abstract: Introduction Dignity therapy is an end‐of‐life psychological intervention that focuses on the creation of a legacy document to alleviate end‐of‐life distress. Dignity therapy is based on an empirical model of dignity at the end of life. Research on dignity therapy has been ongoing for over 12 years in 11 countries, which has created a solid empirical base. Objective This article presents a narrative overview of the literature on dignity therapy to provide a comprehensive narrative review and critical synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(70 citation statements)
references
References 75 publications
2
63
0
5
Order By: Relevance
“…Finally, Bentley, O'Connor, Shaw, and Breen (2017) reviewed the efficacy of DT to alleviate end-of-life distress. In this narrative review Bentley et al (2017) confirmed that DT has been embraced throughout the world and across different population groups, including people who are terminally ill, the elderly, those living with dementia, motor neurone disease or mental illness, or those who are undergoing chemotherapy, and across a variety of formats, including web-based and face-to-face.…”
Section: This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Bentley, O'Connor, Shaw, and Breen (2017) reviewed the efficacy of DT to alleviate end-of-life distress. In this narrative review Bentley et al (2017) confirmed that DT has been embraced throughout the world and across different population groups, including people who are terminally ill, the elderly, those living with dementia, motor neurone disease or mental illness, or those who are undergoing chemotherapy, and across a variety of formats, including web-based and face-to-face.…”
Section: This Special Issuementioning
confidence: 99%
“…Finally, Bentley, O'Connor, Shaw, and Breen (2017) reviewed the efficacy of DT to alleviate end-of-life distress. In this narrative review Bentley et al (2017) confirmed that DT has been embraced throughout the world and across different population groups, including people who are terminally ill, the elderly, those living with dementia, motor neurone disease or mental illness, or those who are undergoing chemotherapy, and across a variety of formats, including web-based and face-to-face. These authors found that while study participants consistently reported high levels of satisfaction and acceptability of DT, the efficacy of DT in alleviating psychological distress at the end-of-life remained unconfirmed (Bentley et al, 2017).…”
Section: This Special Issuementioning
confidence: 99%
“…Similarly, Martinez et al (2017) showed that dignity therapy can effectively improve depression and anxiety in patients. However, Bentley, O'Connor, Shaw, and Breen (2017) indicated that although dignity therapy is well accepted in most cases, it may not always be effective, therapeutically valid, or practical, and may cause family or cultural frictions.…”
Section: Introductionmentioning
confidence: 99%
“…Dignity Therapy is one of the most extensively studied psychological interventions for patients with advanced and terminal disease. Bentley, O'Connor, Shaw, and Breen (2017) have reported findings from a narrative review and critical synthesis of published research on this intervention, which was developed by Chochinov et al (2005). They defined dignity broadly, including a wide range of psychological issues that may be important near the end of life, and constructed the Patient Dignity Inventory (Chochinov et al, 2008) to assess them.…”
mentioning
confidence: 99%